Table of Content - - (Arab Journal for Sciences and Research Publishing, 2025)
:Table of Content• The Role of Digital Transformation in Improving Medical Center Management Efficiency:  Primary Healthcare Centers in Northern Syria as a ModelDr. Hussam Ahmad Hlaak, Dr. Ali Alhousain Aleid , TA. Attia Al-Huseyin• U.S. Interests in the Middle East and the Tools for Their ProtectionMr. Tarek Jarjoura Chahine• A New Paradigm of Institutional South–South Cooperation: Arab Strategies  in the South Pacific and Their Impact on Global GovernanceDr. AI Hexu• Evaluation of Student Achievement Levels:  A Framework for Advancing Academic OutcomesMs. Amera Eid Alsaadi• The Expected Economic Impacts of Sudan's Accession to the WTO:  The Case of the Banking Sector 1970-2008Dr. Abubakr Eltigani Elhag
Keywords: Arab Journal for Sciences & Research Publishing